Odpowiedzi

2009-11-29T17:14:45+01:00
Najlepsza Odpowiedź!
2009-11-29T17:21:52+01:00
A)-3ab(-6a²-2ab-b²)-(3ab³+6a²b²) = -3ab+ 18a³b + 6ab + 3ab³ - 3ab³ - 6a²b² = 18a³b + 6a²b² + 3ab

b)6a(5a²-8b)-10a(6b+7a²)-3ab = 30a³ - 48ab - 60ab -70a³ = -40a³ - 108ab

c)[(8x³-4x²y²)-2(3x²y²+4x³)]*(-2x²y²) = [(8x³-4x²y²) - 6x²y² - 8x³] * (-2x²y²) = [8x³- 4x²y² - 6x²y² - 8x³] * (-2x²y²) = -24x²y² * -2x²y² = 48x⁴y⁴

d)4c-2(c-3)-3[c-3(4-2c)+8] = 4c - 2c + 6 - 3[c - 12 + 6c + 8] = 4c - 2c + 6 - 3c + 36 - 18c - 24 = -19c + 18